Considerations for Cardiovascular Genetic and Genomic Research With Marginalized Racial and Ethnic Groups and Indigenous Peoples: A Scientific Statement From the American Heart Association. (26th July 2021) - Mudd-Martin, Gia; Cirino, Allison L.; Barcelona, Veronica; Fox, Keolu; Hudson, Maui; Sun, Yan V.; Taylor, Jacquelyn Y.; Cameron, Vicky A.; ,
Abstract : Historically marginalized racial and ethnic groups and Indigenous peoples are burdened by significant health inequities that are compounded by their underrepresentation in genetic and genomic research. Of all genome-wide association study participants, ≈79% are of European descent, despite this group constituting only 16% of the global population. For underrepresented populations, polygenic risk scores derived from these studies are less accurate in predicting disease phenotypes, novel population-specific genetic variations may be misclassified as potentially pathogenic, and there is a lack of understanding of how different populations metabolize drugs. Although inclusion of marginalized racial and ethnic groups and Indigenous peoples in genetic and genomic research is crucial, scientific studies must be guided by ethical principles of respect, honesty, justice, reciprocity, and care for individuals and communities. Special considerations are needed to support research that benefits the scientific community as well as Indigenous peoples and marginalized groups. Before a project begins, collaboration with community leaders and agencies can lead to successful implementation of the study. Throughout the study, consideration must be given to issues such as implications of informed consent for individuals and communities, dissemination of findings through scientific and community avenues, and implications of community identity for data governance and sharing. Attention to these issues is critical, given historical harms in biomedical research that marginalized groups and Indigenous peoples have suffered. Conducting genetic and genomic research in partnership with Indigenous peoples and marginalized groups guided by ethical principles provides a pathway for scientific advances that will enhance prevention and treatment of cardiovascular disease for everyone.